Analysis of the Effectiveness and Impact of Less Human Resources in Improving Employee Performance at PT Bank Sumut Syariah KCP Kisaran - Annio Indah Lestari; Dinda Apriliya (Al-Kharaj: Journal of Islamic Economic and Business, 2021)
In carrying out a job, it will be better if it is done together, this is so that the work is completed on time and more effectively. Human resources are an important factor in the success of a company to achieve the expected targets. Employees at Bank Sumut Syariah KCPsy The current range is still minimal so a lot of work is done in duplicate or can be made with multiple positions in order to complete the work in order to achieve the expected target. This is very influential on the performance that is carried out on all employees and really needs some employees (recruitment) to facilitate all activities at the North Sumatra Sharia bank office KCPsy Kisaran.